Pengujian Rasio Keuangan Terhadap Financial Distress: Bukti Di Indonesia - Herbowo Herbowo; Evieana Riesty Saputri (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
This study aims to determine the effect of solvency ratios, activity ratios, and profitability ratios on the financial distress conditions of manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique in this study used purposive sampling. The independent variables in this study are the Debt Ratio, the Total Assets Turn-Over, and the Net Profit Margin. The dependent variable in this study is the condition of financial distress. The results of this study indicate that Total Assets Turn-Over has a significant effect on the financial distress condition, while the Debt Ratio and Net Profit Margin have no significant effect on the financial distress condition of manufacturing companies listed on the Indonesia Stock Exchange. Simultaneously, Debt Ratio, Total Assets Turn-Over, and Net Profit Margin have a significant effect on the financial distress.